Effects of local vibrations on muscle strength and roundhouse kick performance of taekwondo athletes - Oliveira, M.; Rodrigues, S.; Szmuchrowski, L.; Campos, D.; Vieira, L.; Flor, C.; Prudencio, M.; Goncalves, R.; Cuoto, B. (Archives of Budo, 2017)
Background and Study Aim: Exercise with vibration exposure is a type of neuromuscular training that has been used with athletes and non-athletes. The vibration is used in the development of sport performance by applying only oscillatory movements in the human body or the combination of those oscillations with conventional strength training exercises. No studies were found that verified the effects of applying vibration on the performance of the roundhouse kick. Thus, the aim of this study was the knowledge about the effects of the application of mechanical vibration on the muscle strength of the lower limbs and the speed roundhouse kick in taekwondo athletes. Material and Methods: Ten taekwondo athletes (6 males and 4 females) with mean age 18.3 ±2.5, mean body mass 62.1 ± 6.6 kg, mean height 173.3 ±7.0 cm and mean practice time 5.5 ±3.2 volunteered to participate in this study. All the volunteers participated in two different sessions. In both sessions all the volunteers performed a warm up, speed kick pre-test, maximal isometric contraction (MVC) intervention (with or without vibration) and a speed kick post-test. Results: As compared the kick speed values in the pre-test did not differ significantly for any of the values collect in the post-test (immediately: 3, 5 and 8 minutes after intervention). For the maximal force, when compared to the values obtained before the vibration application was verified an acute increase of 56.9 % (p = 0.007) and sub-acute of 12.9 % (p = 0.005), during the vibration exposed and after the interruption of the vibration stimulus, respectively. Conclusions: As expected, these increases were not found in the corresponding times during the MVC performed without vibration. Application of localized vibration can generate increased acute maximum force of members inferiors, but can pass on a reduction in the impulse generated. It was also found that the application of vibration, with the settings for frequency and amplitude have not been able to leverage the speed of shot.